EFFICIENCY OF APPLICATION OF SEMICONDUCTIVE COATINGS FOR REGULATION OF ELECTRIC FIELD IN HIGH-VOLTAGE INSULATION OF ELECTRIC MACHINES - G. V. Bezprozvannych (National Technical University "Kharkiv Polytechnic Institute", 2019)
Introduction. Intensification of competition and the desire to reduce the cost of high-voltage electric machines due to a significant increase in the electrical and thermal loads of the electrical insulation system complicate the operation of anti-corona coatings on the insulation surface of the stator winding and increase the intensity of discharge processes, which significantly reduce the life of the insulation in case of failure of the coatings. Purpose. The analysis of the efficiency of alignment of the electric field along the insulation surface of the stator winding of high-voltage electric machines with semiconductor anti-corona coatings. Methodology. A method for calculating the electric potential distribution along the surface of the winding insulation during the use of semiconductive coatings providing alignment decrease the electric field and eliminating the appearance of moving discharges. The reliability of the calculations is confirmed by experimental studies of the potential distribution over the surface of the anti-corona semiconducting non-linear coating along the frontal part of the samples of the rod of the hydrogenerator for a linear voltage of 20 kV. Practical value. The proposed methodology for calculating the distribution of the electric field over the surface of the insulation and the anti-corona semiconductive coating can be applied to justify the length of the coating in the frontal part of high-voltage electrical machines depending on the electrophysical characteristics of the coating, electrical insulation, and thickness. The results of an experimental verification of the stability of the nonlinear properties of coatings during prolonged electrical and thermal aging of specially made coating samples are presented.